POLITIK, INOVASI, DAN PEMBANGUNAN DESA DI KABUPATEN GUNUNGKIDUL - Kartiwi, Kartiwi; Baidhowah, Adfin Rochmad; Wenggi, Karolina (Fakultas Politik Pemerintahan, 2022)
Innovation has become an inevitable concept in today's development policy. However, innovation in development is an idea that is often used by political actors for their political agenda. By using qualitative methods, this research aims to find out how the political aspect in Nglanggeran Village, Gunungkidul Regency is framing this innovation. We found that the innovations that have been carried out by the village become a bargaining position for the village if there is an election for both village heads and regional heads. The majority of candidates will state their commitment to support the development of innovations carried out. Politicians do not promise to do innovation A or B but to support existing and future innovations.